In Situ Noninvasive Observation of Nitric Oxide Fluctuation in SARS-CoV-2 Infection In Vivo by Organic Near-Infrared-II Fluorescent Molecular Nanoprobes - Tang, Yufu (AMER CHEMICAL SOC, 2023)
10.1021/acsnano.3c05410